Meaning and its Effect on the Grammatical Guidance of (Gareebul Hadith): Al-zamakhshari’s book Alfa’iq as a case study - Khaimar, Atef Ahmed Osman (Journal of Humanities & Social Sciences, 2020)
This research is based on the explanation of the meaning and its types and the need to understand it, and the concept of the parsing (Al-i’raab) and its importance, and the relationship between meaning and parsing (Al-i’raab), it also aims to demonstrate the grammatical guidance of (Gareebul Hadith), and its effect according to Zamakhshari, and reveal the manifestations of this effect, and expounding the basis of weighting according to him in case of multifaceted aspects of parsing (Al-i’raab). It also aims to reveal the role of meaning in his grammatical thought. To achieve these objectives, the research relied on analytical descriptive approach, and the required discussion, analysis and comment, in order to reach the scientific truth impartially and objectively. The nature of the subject necessitated that it be composed of two topics interceding an introduction and a conclusion. The first topic defined the meaning and parsing (Al-i’raab), and explained the relationship between them, through three sections addressing the concept of the meaning and the need to understand it, the concept of the parsing (Al-i’raab) and its importance, the relationship between the meaning and the parsing (Al-i’raab). The second topic showed the manifestations of the effect of the meaning in the grammatical guidance of (Gareebul Hadith) according to Zamakhshari, and it came in two sections; one dealt with what was attributed to the meaning in which the main touchstone in the grammatical guidance, and the latter studied what is likely with multifaceted aspects of parsing (Al-i’raab). One of the most important results of the research is that Zamakhshari not only in his grammatical guidance of (Gareebul Hadith) mentioned grammatical functions, but went beyond that to the semantic meaning, and the role of context in highlighting that meaning. The research also shows the effect of meaning according to Zamakhshari in mentioning the grammatical aspects allowable, and the differentiation between them is according to the power of meaning in each aspect. Among the recommendations of the researcher: The need to link between the Grammar and meaning, or between grammatical and semantic phenomena.